2013
DOI: 10.1128/jb.02000-12
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Yersinia pestis PhoP-PhoQ Regulatory System in the Flea and Its Role in Producing a Transmissible Infection

Abstract: cTransmission of Yersinia pestis is greatly enhanced after it forms a bacterial biofilm in the foregut of the flea vector that interferes with normal blood feeding. Here we report that the ability to produce a normal foregut-blocking infection depends on induction of the Y. pestis PhoP-PhoQ two-component regulatory system in the flea. Y. pestis phoP-negative mutants achieved normal infection rates and bacterial loads in the flea midgut but produced a less cohesive biofilm both in vitro and in the flea and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 84 publications
3
79
0
Order By: Relevance
“…It seems plausible that yfbA may control the expression of a still unidentified biofilm or colonization factor. Similar phenotypes have been reported for two regulatory factors, PhoP (a two-component response regulator) and Hfq (a bacterial RNA binding protein) when studying biofilm formation in the rat flea (55,56).…”
Section: Discussionmentioning
confidence: 60%
“…It seems plausible that yfbA may control the expression of a still unidentified biofilm or colonization factor. Similar phenotypes have been reported for two regulatory factors, PhoP (a two-component response regulator) and Hfq (a bacterial RNA binding protein) when studying biofilm formation in the rat flea (55,56).…”
Section: Discussionmentioning
confidence: 60%
“…Taken together, our data point to a novel role for WecE in polymyxin B resistance and suggest that Y. pestis has evolved additional mechanisms of CAMP resistance that are distinct from those of other currently described systems. Rebeil et al (2013) recently demonstrated that Y. pestis mutants deficient in their ability to modify LPS with Ara4N were able to maintain long-term infections in fleas (4 weeks) and develop proventricular blockages. This initially appears to contrast with our data, which show that Ara4N modification is important for survival of Y. pestis in the early stages of flea infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ability of Y. pestis to form stable biofilms is important in its ability to block fleas and thus be transmitted by the classic route. The hms, gmhA and phoPQ genes are necessary for flea blockage through their involvement in biofilm formation (Darby et al, 2005;Hinnebusch et al, 1996;Jarrett et al, 2004;Rebeil et al, 2013). Although these genes play important roles in the association of Y. pestis with fleas, they do not fully explain the organism's ability to survive in arthropods and undergo successful transmission (Eisen et al, 2006;Hinnebusch et al, 1996;Houhamdi & Raoult, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the PhoPQ regulon responds to low Mg 2+ and is not considered to be activated extracellularly. However, PhoPQ has been shown to play a role in biofilm formation in the flea, and in subsequent transmission (Rebeil et al, 2013), where the bacteria exist extracellularly. The presence of multiple magnesium transporters indicates that different transporters may be important at different stages of infection, and the interplay of these redundant systems in vivo has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%